2020
DOI: 10.1093/geronb/gbaa117
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbating Inequalities: Social Networks, Racial/Ethnic Disparities, and the COVID-19 Pandemic in the United States

Abstract: Objectives The disruption and contraction of older adults’ social networks are among the less-discussed consequences of the COVID-19 pandemic. Our objective is to provide an evidence-based commentary on racial/ethnic disparities in social network resources and draw attention to the ways in which disasters differentially impact social networks, with meaningful insight for the ongoing pandemic. Methods We draw upon prior resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(125 citation statements)
references
References 28 publications
(29 reference statements)
6
107
1
5
Order By: Relevance
“…Although our institutions are a level 1 pediatric trauma center and regional burn center in a large metropolitan area, it is possible that our data does not encompass the true nature of trauma patterns during the pandemic. Children from differing socioeconomic or racial groups may be less likely to present to large hospital systems owing to disproportionate impact of COVID-19 among minorities [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] . Our literature review has found that there is deeply rooted skepticism, especially within the Black and immigrant communities, toward the medical establishment.…”
Section: Discussionmentioning
confidence: 99%
“…Although our institutions are a level 1 pediatric trauma center and regional burn center in a large metropolitan area, it is possible that our data does not encompass the true nature of trauma patterns during the pandemic. Children from differing socioeconomic or racial groups may be less likely to present to large hospital systems owing to disproportionate impact of COVID-19 among minorities [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] . Our literature review has found that there is deeply rooted skepticism, especially within the Black and immigrant communities, toward the medical establishment.…”
Section: Discussionmentioning
confidence: 99%
“…As a first attempt in identifying potential host genetic risk factors associating with COVID-19 mortality, it is reasonable for us to focus on genetic signals given the complexity of the preexisting conditions, but incorporating such information into association studies is a valid direction. Third, the impact of social and economic disparities on COVID-19 susceptibility has been well documented [53,54]. Although our study aims to identify genetic risk factors for COVID-19 mortality, further research is needed to determine how genetic factors may interact with environmental factors that influence access to high-quality health care.…”
Section: Discussionmentioning
confidence: 99%
“…It appeared that the young adult group was driving the relationships between the ageism variable and the responses to the pandemic; however, age group did not moderate any of these links, suggesting that younger and older adults had similar relationships between ageism and responses to the pandemic (the results of these moderations can be found in Supplementary Table 2). Differences among the focal constructs were explored across multiple participant background characteristics that have been noted to influence reactions the COVID-19 pandemic (Barber and Kim, 2020;Campos-Castillo, 2020;Garcia et al, 2020;Gauthier et al, 2020). These factors included age group (younger adult vs. older adult), gender (male vs. female), race (White vs. non-White), level of education, recruitment source (social media vs. MTurk), state of residency (Ohio vs. other), political affiliation, and essential worker status.…”
Section: Descriptive Statistics and Control Variablesmentioning
confidence: 99%